Children's consumption behavior in response to food product placements in movies. Issue 2 (3rd February 2015) - Matthes, Jörg; Naderer, Brigitte
Abstract Almost all research on the effects of product placements on children has focused on brand attitudes or behavioral intentions. Drawing on the important difference between attitudes or behavioral intentions on the one hand and actual behavior on the other, this paper tests the effects of brand placements on children's food consumption. Children from 6 to 14 years old were exposed to an excerpt of the popular movie Alvin and the Chipmunks, including placements for the product Cheese Balls. Three versions were created: one without placements, one with moderate placement frequency, and one with high placement frequency. Results showed that exposure to high‐frequency product placements exerted a significant effect on snack consumption, but no effect on brand or product attitudes. These effects were independent of children's ages. The findings are of great importance to consumer behavior scholars, nutrition experts, and policy regulators. Copyright © 2015 John Wiley & Sons, Ltd.